Vitamin D Deficiency and Janus kinase 2 V617F Mutation Status in Essential Thrombocythemia and Polycythemia Vera - Yikilmaz, Aysun Şentürk (Malays J Med Sci, 2020)
INTRODUCTION: Vitamin D, which is known for its effects on calcium and bone metabolism, has recently been associated with haematological malignancies. We aimed to investigate the relationship between disease findings and vitamin D deficiency in essential thrombocythemia (ET) and polycythemia vera (PV). MATERIAL AND METHODS: This retrospective cohort study conducted in Turkey included 73 patients diagnosed with PV or ET according to WHO criteria between 2012 and 2018. Vitamin D deficiency was defined as 25-OH vitamin D < 20 ng/mL. Polymerase chain reaction (PCR) was used to detect the Janus kinase 2 (JAK2) V617F mutation. RESULTS: Vitamin D deficiency was found in 66.7% of PV and 74.2% of ET patients. The median follow-up time of ET and PV patients was 48 months and 47 months, respectively. Patients with the JAK2 mutation had a higher prevalence of a history of thrombosis and age older than 65 years. There was a significant relationship between JAK2 positivity and vitamin D deficiency. CONCLUSION: There was a remarkably higher prevalence of vitamin D deficiency in JAK2 mutation-positive ET and PV patients. These patients should be carefully evaluated for vitamin D deficiency. More studies are required to further investigate the association between JAK2 and vitamin D.